2022
DOI: 10.3390/ma15186341
|View full text |Cite
|
Sign up to set email alerts
|

Surface Evaluation of Aligners after Immersion in Coca-Cola and Orange Juice

Abstract: Orthodontic removable appliances made of transparent thermoplastic materials—aligners—are becoming increasingly popular in contemporary orthodontic practice. It is important for the clinician to fully understand the mechanical properties and behavior of the appliance used. Because of that, the aim of our study was to investigate the changes in aligner surface after immersion in Coca-Cola and orange juice. For surface evaluation, fractal analysis, texture analysis, and wetting angle measurement were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It should indeed be considered that the aging method adopted by Pratsinis et al [ 54 ] and Willi et al [ 55 ], only involving aqueous immersion of the aligner, underestimated the effect on resin degradation and leaching of the factors acting intraorally, such as pH, temperature, bacterial and enzymatic activity, occlusal and masticatory forces [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should indeed be considered that the aging method adopted by Pratsinis et al [ 54 ] and Willi et al [ 55 ], only involving aqueous immersion of the aligner, underestimated the effect on resin degradation and leaching of the factors acting intraorally, such as pH, temperature, bacterial and enzymatic activity, occlusal and masticatory forces [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should, however, be mentioned that all the biocompatibility tests were based on substances released from the specimens by passive hydrolysis and failed to assess the effects of intraoral influential factors, such as salivary enzymes, functional and parafunctional loads, temperature variations, pH changes such as those related to the consumption of soft drinks or juices [ 57 ], microbial activity. Such experiments omit to evaluate the challenge of the oral environment on polymers degradation and are only useful to compare 3D-printed appliances with other commercially available or conventionally manufactured devices.…”
Section: Discussionmentioning
confidence: 99%
“…One of these external factors is food and beverages. Warnecki et al [ 22 ] confirmed that acidic drinks, such as coca cola and orange juice, can damage the structure of the clear aligners’ splints. Damage to the structure would impair tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that the properties of these materials deteriorate over time, not only because of external conditions, but also due to material wear. This phenomenon also occurs in 3D-printable dental materials [ 22 , 34 ]. Although this was not the subject of the present investigation, future investigations should consider these aspects as an interesting path in this developing branch of dentistry.…”
Section: Limitationsmentioning
confidence: 97%
“…This could influence the material's surface. Moreover, the use of beverages and food as well as bleaching, damages the surface of the materials applied in dentistry [22,23]. The color change is also observed when cigarette smoke is an influencing factor [24].…”
Section: Discussionmentioning
confidence: 99%